The Role of Caregiver-Reported Risks in Predicting Adverse Pediatric Outcomes. (24th July 2020) - Vaz, Louise E; Wagner, David V; Jungbauer, Rebecca M; Ramsey, Katrina L; Jenisch, Celeste; Koskela-Staples, Natalie; Everist, Steven; Austin, Jared P; Harris, Michael A; Zuckerman, Katharine E
Abstract: Objective: Certain social risk factors (e.g., housing instability, food insecurity) have been shown to directly and indirectly influence pediatric health outcomes; however, there is limited understanding of which social factors are most salient for children admitted to the hospital. This study examines how caregiver-reported social and medical characteristics of children experiencing an inpatient admission are associated with the presence of future health complications. Methods: Caregivers of children experiencing an inpatient admission ( N  =   249) completed a predischarge questionnaire designed to capture medical and social risk factors across systems (e.g., patient, caregiver, family, community, healthcare environment). Electronic health record (EHR) data were reviewed for child demographic data, chronic disease status, and subsequent emergency department visits or readmissions (i.e., acute events) 90 days postindex hospitalization. Associations between risk factors and event presence were estimated using odds ratios (ORs) and confidence intervals (CI), both unadjusted and adjusted OR (aOR) for chronic disease and age. Results: Thirty-three percent ( N  =   82) of children experienced at least one event. After accounting for child age and chronic disease status, caregiver perceptions of child's health being generally "poor" or "not good" prior to discharge (aOR = 4.7, 95% CI = 2.3, 9.7), having high care coordination needs (aOR = 3.2, 95% CI = 1.6, 6.1), and experiencing difficulty accessing care coordination (aOR = 2.5, 95% CI = 1.4, 4.7) were significantly associated with return events. Conclusions: Caregiver report of risks may provide valuable information above and beyond EHR records to both determine risk of future health problems and inform intervention development.